Clinical significance of copy number variants involving KANK1 in patients with neurodevelopmental disorders. - Twede, Hope (European Journal of Medical Genetics, 2018)
Copy number variants (CNV)s involving KANK1 are generally classified as variants of unknown significance. Several clinical case reports suggest that the loss of KANK1 on chromosome 9p24.3 has potential impact on neurodevelopment. These case studies are inconsistent in terms of patient phenotype and suspected pattern of inheritance. Further complexities arise because these published reports utilize a variety of genetic testing platforms with varying resolution of the 9p region; this ultimately causes uncertainty about the impacted genomic coordinates and gene transcripts. Beyond these case reports, large case-control studies and publicly available databases statistically cast doubt as to whether variants of KANK1 are clinically significant. However, these large data sources are neither easily extracted nor uniformly applied to clinical interpretation. In this report we provide an updated analysis of the data on this locus and its potential clinical relevance. This is based on a review of the literature as well as 28 patients who harbor a single copy number variant involving KANK1 with or without DOCK8 (27 of whom are not published previously) identified by our clinical laboratory using an ultra-high resolution chromosomal microarray analysis. We note that 13 of 16 patients have a documented diagnosis of autism spectrum disorder (ASD) while only two, with documented perinatal complications, have a documented diagnosis of cerebral palsy (CP). A careful review of the CNVs suggests a transcript-specific effect. After evaluation of our case series and reconsideration of the literature, we propose that KANK1 aberrations do not frequently cause CP but cannot exclude that they represent a risk factor for ASD, especially when the coding region of the shorter, alternate KANK1 transcript (termed “transcript 4” in the UCSC Genome Browser) is impacted.